Space Facility Reservation System for Rakan Muda Larut Matang and Selama office / Nor Azura Hazlina Kamis - Kamis, Nor Azura Hazlina (2020)
Space Facility Reservation System for Larut Matang and Selama office is a web-based system where the customers can make the reservation process via online. This system also helps the staff and manager to manage the reservation and facility information systematically and efficiency. It is proposed as an alternative for the community to make the reservation. After the findings, the result found that the company faced the problems to manage the reservation process. Rakan Muda Larut and Selama office needs a computerized database system to manage reservation data and online technology is a good way to reach a wider customer base, hi developing this system. System Development Life Cycle (SDLC) will be used as a method to guide in developing the system. The model for Space Facility Reservation System for Larut Matang and Selama office is Adapted Waterfall Model which has six phases which is system planning, system analysis, system design, system development, system testing and evaluation and system documentation. Moreover, the system testing and user evaluation has been conducted in order to identify the functionality and usability of the system. For the functionality testing it involve the testing based on the scenario. The scenario that involve is normal scenario and exception scenario while to measure the usability of the system, the ISO (International Organization for Standardization) approach will be used that consist to measure the effectiveness, efficiency and satisfaction. The user evaluation involves 3 users as a tester to evaluate the usability of system. As a result, the effectiveness of the system is 80% which is the users agree that the system is easy to used. Then, the result for the efficiency can be measured using time-based efficiency and overall relative efficiency while the result for the satisfaction are 85% which is the user are satisfied when using the system.